Implementasi Kombinasi Model Pembelajaran PBL, NHT dan STAD Dalam Meningkatkan Keterampil Kerja Sama Siswa Kelas 5 SDN Roham Raya - Okta Riyan Dwi Saputra; Celia Cinantya (Lembaga Bale Literasi, 2026)
This study aims to determine the extent to which the combination of PBL, NHT and STAD learning models in an effort to improve cooperation skills in elementary school students in grade V (five) of SDN Roham Raya. The subjects of this study were a small group of 14 students in grade V of SDN Roham Raya with relatively low skill ability criteria. Classroom action research (CAR) was conducted in grade V of SDN Roham Raya totaling 14 students. This study used a combination of PBL, NHT, and STAD learning models. The results of the study obtained data at the last meeting at meeting 4, namely with the criteria that all students were skilled with a percentage of 100% of the total 14 students who were research subjects, using a combination of learning models that had been previously selected by the researcher. It can be concluded that in an effort to improve students' cooperation skills, it can be improved using a combination of PBL, NHT and STAD learning models